Titanium, zirconium and vanadium conversion coatings (TZVCCs) on AZ91D magnesium alloy sheets. (12th August 2020) - Zhu, Wen; Chen, Furui; Yi, Aihua; Liao, Zhongmiao; Li, Wenfang; Li, Kang; Chen, Ken; Liang, Guofeng; Guo, JinTao; Wu, Qing
Abstract: This paper reports the preparation, characterization, and corrosion resistance of an eco-friendly titanium/zirconium/vanadium-based conversion coating (TZVCC) on an AZ91D magnesium alloy sheet. The TZVCC microstructure and composition were investigated by SEM, EDS, and XPS. The corrosion behavior of treated and untreated magnesium alloy sheets was observed by potentiodynamic polarization and EIS. The coatings are found to be rapidly formed on the alloy exterior within 90 s and optimal conversion treatment time at 50 s. The primary components of the TZVCC were MgO, Mg(OH)2, V2 O5, V2 O3, MgF2, TiO2, ZrO2 and metal-organic complexation. The coating was also shown to markedly enhance the corrosion resistance performance of magnesium alloys.